2021
DOI: 10.1002/ep.13767
|View full text |Cite
|
Sign up to set email alerts
|

Performance of roof‐cool paints prepared using organic acrylic polymer binder and inorganic additives for the thermal reduction in buildings

Abstract: The passive cooling strategy has gained significant attention in recent years due to the dreadful impact of active cooling on energy demand and global warming. This work reports on preparing water‐based new roof‐cool paints and studying their utility on thermal and reflectivity performance. The acrylic binder was synthesized via free‐radical water‐based emulsion polymerization using vinyl acrylic monomers ‐three new paint formulations prepared using the as‐prepared acrylic polymer binder with inorganic pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…17 ambient temperature. 18 Sun et al prepared a typical polydimethylsiloxane composite containing 20 wt % of silica/ titanium dioxide (3/7) compound filler and found that this coating showed relatively higher solar reflectivity (0.91) and atmospheric transparent window emissivity (0.83), leading to a cooling effect of 5.3 °C in an outdoor cooling test. 19 Although the addition of multiple functional fillers can enhance the radiative cooling ability of polymer-based materials, large amounts of fillers must be added to achieve an acceptable cooling effect due to the inherent poor compatibility between inorganic filler and polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 ambient temperature. 18 Sun et al prepared a typical polydimethylsiloxane composite containing 20 wt % of silica/ titanium dioxide (3/7) compound filler and found that this coating showed relatively higher solar reflectivity (0.91) and atmospheric transparent window emissivity (0.83), leading to a cooling effect of 5.3 °C in an outdoor cooling test. 19 Although the addition of multiple functional fillers can enhance the radiative cooling ability of polymer-based materials, large amounts of fillers must be added to achieve an acceptable cooling effect due to the inherent poor compatibility between inorganic filler and polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of functional fillers with high refractive index (e.g., titanium dioxide, zirconium dioxide, zinc oxide) and wide electron band gap (e.g., alumina, silica, barium sulfate) into the polymer matrix is regarded as a cost-effective way to achieve efficient subambient radiative cooling. For example, Dias et al claimed that the addition of 50 vol % titanium dioxide can remarkably enhance the solar reflectance of acrylic coating with maximum values of ∼0.9 . Suwal and Ramaswamy fabricated acrylic composite coating with 40 wt % of titanium dioxide and mica powders as roof-cool paints; such composite coating exhibited a synergistic effect in reflecting the incident light, resulting in a 2.4 °C reduction of internal ambient temperature . Sun et al prepared a typical polydimethylsiloxane composite containing 20 wt % of silica/titanium dioxide (3/7) compound filler and found that this coating showed relatively higher solar reflectivity (0.91) and atmospheric transparent window emissivity (0.83), leading to a cooling effect of 5.3 °C in an outdoor cooling test .…”
Section: Introductionmentioning
confidence: 99%
“…Passive-cooling technology has proven that it is a low-cost, green cooling method to achieve indoor cooling for buildings without additional energy consumption [7][8][9][10]. However, the cooling capability of this method was not significant.…”
Section: Introductionmentioning
confidence: 99%